Substance use in youth - Hussain Ali Pachani, Nazish (International Journal of Endorsing Health Science Research, 2016)
Youth is the time period of vast exploration and curiosity. Young people begin to explore the world around. They acquire pleasure and satisfaction by carrying out risky behaviors to satisfy their impulse. Substance use is one such action that young people get attraction from certain individual, familial, social and environmental variables. Young people's past as well as present stressful experience and maladaptive coping style create strong affinity. Diverse researches have favored that pubertal transition, parenting style, family cohesiveness, maternal use, modeling, conditioning, and socialization reflect on youth's upbringing. It is evident that the substance use is one of the cognitive and behavioral outcome. There is a need to construct a most supportive zone around youth that enables them to broader their horizon of emotional intelligence. As a health care professional, knowledge about all the levels of prevention can aid communities to have an addiction free environment. Individual counselling, family therapy, national and international awareness programs would help in eradicating substance use. Collaborative work of Governmental and Non-Governmental Organizations (NGO’s) would motivate youth to acquire a substance free lifestyle.